If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + (4 + 2) = 2x + -1(7x + -4) + 5 Combine like terms: 4 + 2 = 6 6x + (6) = 2x + -1(7x + -4) + 5 6x + 6 = 2x + -1(7x + -4) + 5 Reorder the terms: 6 + 6x = 2x + -1(7x + -4) + 5 Reorder the terms: 6 + 6x = 2x + -1(-4 + 7x) + 5 6 + 6x = 2x + (-4 * -1 + 7x * -1) + 5 6 + 6x = 2x + (4 + -7x) + 5 Reorder the terms: 6 + 6x = 4 + 5 + 2x + -7x Combine like terms: 4 + 5 = 9 6 + 6x = 9 + 2x + -7x Combine like terms: 2x + -7x = -5x 6 + 6x = 9 + -5x Solving 6 + 6x = 9 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 6 + 6x + 5x = 9 + -5x + 5x Combine like terms: 6x + 5x = 11x 6 + 11x = 9 + -5x + 5x Combine like terms: -5x + 5x = 0 6 + 11x = 9 + 0 6 + 11x = 9 Add '-6' to each side of the equation. 6 + -6 + 11x = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 11x = 9 + -6 11x = 9 + -6 Combine like terms: 9 + -6 = 3 11x = 3 Divide each side by '11'. x = 0.2727272727 Simplifying x = 0.2727272727
| 4x^2+x=-3 | | (9rt)2= | | 10x-5=-8x+7 | | V^2-3v=3 | | 5x+1=4x-4 | | -(8y+5)-(-7y-7)=-4 | | 10s-3=12 | | 4x+20+2x+34=-27 | | 11=8x+10-5x+5 | | -6x+2.5+8x+1.2=30.9 | | x^2-1=3 | | x^2+1=-2 | | 17x^2+3-[3(x^2-7)+8]= | | 135x-x=40200 | | 10x-5-4x+8=-27 | | 1.5x-3.3=0.8x+0.13 | | 12=8x+4-6x-10 | | 3x-9+3x=39 | | (X+1)+7=70 | | (5n+7n)-(9n-4n+3)= | | 14=12x+8 | | 3x-18+2=4x+8-21 | | 3x-6+2=4x+8-21 | | 3x-6+2=4x+2-21 | | (2x+25)=104 | | (21-6x)=37 | | 12x+8=3(-9x+1) | | -4x=-56 | | 12x+8=(-9x+1) | | 2y^2-4y-14-y^2=0 | | 6+16s-1=8s+71-3s | | 3w^2+3w-35=0 |